QOL-23. Expanded protocols for hearing loss related cisplatin-based therapy in childhood cancer patients. (3rd June 2022) - Grosnik, Amy; Graham, Richard T; Pillay-Smiley, Natasha; de Blank, Peter; Hummel, Trent; Mochizuki, Aaron; Raskin, Scott; Windmill, Ian
Abstract: BACKGROUND: Most children who require cisplatin chemotherapy incur hearing loss. The basal end of the cochlea, corresponding to high frequency sound perception, is typically affected first, with progression along the basilar membrane and to lower frequencies over time. Typical audiologic protocols for children are often restricted to the speech frequencies (500-4000Hz). However, reliable responses to higher frequencies can be obtained using specialized electrophysiologic measures or adapted behavioral test procedures, which may lead to earlier identification of hearing loss during ototoxicity monitoring. METHODS: Auditory Brainstem Response (ABR) and behavioral threshold assessments were completed for patients during cisplatin treatment at Cincinnati Children's Hospital between 2017 and 2021. High frequency ABR protocols were established to include 6000 and 8000 Hz and behavioral testing protocols were expanded to include frequencies 8000 through 16000 Hz. Hearing loss was defined as >20 dB eHL at any frequency. The typical and high frequency protocols were compared to determine if higher frequency measurement provides a more sensitive means to detect the onset of hearing loss. RESULTS: One-hundred and fifty-three patients receiving cisplatin were assessed audiometrically. For patients who required ABR evaluations, 38% were identified with hearing loss when using the typical test protocol, where 79% of the patients were identified with hearing loss when using the high frequency protocol. For patients who were able to complete behavioral audiometric evaluations, 42% were identified with hearing loss with the typical protocol while 84% were identified with the high frequency protocol. CONCLUSIONS: The addition of higher frequencies to audiologic evaluation protocols for both ABR and behavioral audiometry significantly increases sensitivity to detect hearing loss during ototoxicity monitoring of cisplatin treatment and is a feasible strategy in pediatric cancer patients. Audiologically, the increased sensitivity to detect hearing loss may lead to earlier intervention regarding hearing and communication for the patient/family.